2005
DOI: 10.1016/j.amjhyper.2005.05.031
|View full text |Cite
|
Sign up to set email alerts
|

G-6A Polymorphism of the Angiotensinogen Gene and Its Association With Left Ventricular Mass in Asymptomatic Young Adults from a Biethnic CommunityThe Bogalusa Heart Study

Abstract: Background: Angiotensinogen (AGT), the precursor of angiotensin II and a rate limiting factor in the reninangiotensin system, is implicated in left ventricular hypertrophy, as angiotensin II is a potent stimulator of cardiac growth. A genetic variant (G-6A) in the proximal promoter region of the AGT gene may be particularly important for changes in left ventricular mass (LVM). However, previous findings associating this variant with LVM among relatively older adults with cardiovascular morbidity are inconsiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…The authors made a conclusion that particular background including age, gender and ethnical factors can lead to this genotype impacting LVH development. Correlation between the A allele and LVH was also confirmed by an American study, showing differences between ethnical groups too [24]. Our study also revealed prevalence of the A allele in patients below 50 years old with LVH (50% vs 46%), but distinctions were insignificant.…”
Section: Clinical and Genetic Factors Of Left Ventricular Hypertrophysupporting
confidence: 70%
See 1 more Smart Citation
“…The authors made a conclusion that particular background including age, gender and ethnical factors can lead to this genotype impacting LVH development. Correlation between the A allele and LVH was also confirmed by an American study, showing differences between ethnical groups too [24]. Our study also revealed prevalence of the A allele in patients below 50 years old with LVH (50% vs 46%), but distinctions were insignificant.…”
Section: Clinical and Genetic Factors Of Left Ventricular Hypertrophysupporting
confidence: 70%
“…Авторы сделали вывод о том, что данный генотип оказывает влияние на раз-витие ГЛЖ в определенных условиях и зависит от воз-раста, пола, этнических факторов. В американском исследовании также была подтверждена взаимосвязь между А аллелем и ГЛЖ, причем также выявлены от-личия в этнических группах [24]. В нашем исследова-нии при анализе возрастной группы пациентов до 50 лет также обнаружено преобладание аллеля А у больных с ГЛЖ (50% против 46%), однако различие не было ста-тистически значимым.…”
Section: Clinical and Genetic Factors Of Left Ventricular Hypertrophyunclassified
“…Therefore, polymorphisms located in coding or promoter regions of AGT may be upstreaming effectors of RAS for sHF. In the previous association studies of the AGT gene with sHF, G-6A and M235T polymorphism were thought to be related with sHF [4,5]. That is because the M235T polymorphism has been found to be associated with the elevation of plasma AGT levels in some Caucasian populations and the G-6A variant is in close linkage disequilibrium with the M235T polymorphism [6].…”
Section: Introductionmentioning
confidence: 99%
“…There is also some, but not yet rigorous evidence for the relevance of angiotensinogen (AGT) gene to LVH level [Jeng et al, 1999;Makeeva et al, 2004;Patel et al, 2005]. However, such a link between these genetic polymorphism and LVH has not been confirmed in other populations [Fernandez, et al, 1998;Kauma et al, 1998, Shlyakhto et al, 2001.…”
Section: Left Ventricular Hypertrophy and Genetics Of Renin-angiotensmentioning
confidence: 96%